Optimization of Biodiesel Production from Sludge of Mask Waste and Used Cooking Oil Using Lipase as Biocatalyst - Baiq Repika Nurul Furqan; Muhammad Rizal Januardi (Biota, 2023)
Mask waste and used cooking oil contain hydrocarbons and free fatty acids. the combination of these ingredients with pretreatment heating in the microwave and the help of lipase enzymes makes the resulting sludge has the potential to be converted into biodiesel with a maximum yield when compared to making biodiesel from other materials and methods. The results of this study indicate that pre-treated sludge from mask waste and used cooking oil can be converted into biodiesel through a methanol transesterification reaction with the help of thermostable lipase enzymes from Pseudomonas. As for the optimum conditions, the highest biodiesel yield was produced at a temperature of 60℃, the best reaction time was 25 minutes, the volume of sludge was 10 mL and the optimum pH was at pH 8. The flame test on the biodiesel produced had been carried out, most of which had bright blue, red flames and orange. There are also some results that the flame is dim and even the test results are not lit.